Nanostructured coated powders for structural net shape components - Castanho, J. M. (2007)
The specific goal of the present study is to evaluate the surface performance of thin films based on sputtered stainless steel (304 AISI) deposited on dissimilar (Cu) and similar powder materials (316 AISI) with different size distributions and shapes. The covering efficiency, the surface morphology and the grain size, and their impact on the flowability of powders, are studied. The most important role of powder surface treatments is attained when spherical powders of copper were coated with a nanocrystalline thin film of stainless steel, the flowability increases by 80%. However, in the stainless steel powders the presence of a similar coating has relevance only for irregular particles, where a 25% flowability improvement is measured.